CUSTOM PROCEDURES ON TRADE IN MACAO CHALLENGES AND OPPORTUNITIES - Cheang, Hon Meng (2025)
This dissertation examines the customs procedures governing trade in Macao, a Special Administrative Region of China, focusing on their role in facilitating trade within the Greater Bay Area. Adopting a qualitative approach, the study conducts in-depth interviews with stakeholders, including local businesses, customs officials, and trade experts, to identify factors affecting the efficiency and transparency of customs processes, such as clearance, licensing, and declarations. The research is significant as it enriches the theoretical framework of trade facilitation in Macao, where literature is scarce, and provides practical insights for customs authorities and traders. Findings reveal bureaucratic complexities, technological gaps, and documentation burdens, particularly impacting small and medium enterprises. Three additional factors influencing trade efficiency—regional integration, stakeholder coordination, and policy alignment—are identified. The study recommends streamlined licensing, enhanced digital systems, and SME-focused training to foster sustainable trade development. These insights offer actionable guidance for policymakers and practitioners to strengthen Macao’s position as a regional trade hub.